Influence of Incentive Design and Organizational Characteristics on Wellness Participation and Health Outcomes. Issue 10 (October 2020) - Grossmeier, Jessica; Mangen, David J.; Anderson, David R.; Gingerich, Stefan B.; Mitchell, Rebecca J.; Imboden, Mary T.; Kaplan, Gordon D.; Gascon, Gregg M.; Serxner, Seth A.; Bodak, Tony
Abstract : Objective: To explore how changing incentive designs influence wellness participation and health outcomes. Methods: Aggregated retrospective data were evaluated using cluster analysis to group 174 companies into incentive design types. Numerous statistical models assessed between-group differences in wellness participation, earning incentives, and over-time differences in health outcomes. Results: Four incentive design groups based on requirements for earning incentives were identified. The groups varied in support for and participation in wellness initiatives within each company. All four design types were associated with improved low density lipoprotein (LDL) ( P  < 0.01), three with improved blood pressure ( P  < 0.001), and two with improved fasting glucose ( P  < 0.03). No incentive plan types were associated with improved body mass index (BMI), but designs predominantly focused on health outcomes (eg, Outcomes-Focused) exhibited a significant increase over time in BMI risk. Conclusion: Incentive design and organizational characteristics impact population-level participation and health outcomes.